2001
DOI: 10.1002/syn.10025
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microdialysis and conditioned place preference studies in rats are consistent with abuse potential of tramadol

Abstract: The abuse potential of tramadol was investigated using both in vivo microdialysis measures of dopamine (DA) release within the nucleus accumbens (NAc) shell and the conditioned place preference (CPP) paradigm in rats. Tramadol (75 mg/kg, i.p.) induced a statistically significant increase (starting 80 min posttreatment) in DA release within the NAc shell, which was maintained for at least 120 min posttreatment. Tramadol (18.75, 37.5, and 75 mg/kg i.p.) produced a statistically significant CPP, with the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…More recently, however, tramadol was shown to produce conditioned place preference in rats (Sprague et al, 2002;Tzschentke, Bruckmann, & Friderichs, 2002). The effects of tramadol on place preference were similar in magnitude to those of morphine, which served as a positive control in each study.…”
Section: Results Of Animal Studiesmentioning
confidence: 87%
“…More recently, however, tramadol was shown to produce conditioned place preference in rats (Sprague et al, 2002;Tzschentke, Bruckmann, & Friderichs, 2002). The effects of tramadol on place preference were similar in magnitude to those of morphine, which served as a positive control in each study.…”
Section: Results Of Animal Studiesmentioning
confidence: 87%
“…Ordinate: mean differences in time spent in the preferred place between postconditioning and preconditioning. Immediately after s.c. injection of tramadol or M1, mice were placed and conditioned in either compartment for 1 h. Each column represents the mean±SEM of seven to eight mice the investigation on abuse potential of tramadol (Sprague et al 2002;Tzschentke et al 2002). We found that both tramadol and M1 produced a significant place preference in mice, and these effects were significantly suppressed by pretreatment with the MOR antagonist β-FNA.…”
Section: Discussionmentioning
confidence: 95%
“…These findings suggest the possibility that pain could lead to physiological changes at supraspinal levels associated with the suppression of opioid dependence. It has been reported that tramadol has a potential for physical and psychological dependence (Yanagita 1978;Liu et al 1999;Sprague et al 2002;Tzschentke et al 2002), but may possess considerably less abuse potential than morphine (Budd 1994). Recent clinical evidence has suggested that tramadol abuse has been suggested in humans (Cicero et al 1999;Yates et al 2001;Zacny 2005;Epstein et al 2006).…”
Section: Introductionmentioning
confidence: 94%
“…However, there are some arguments about the abuse potential of TRAM. Some investigations have reported that TRAM leads to abuse (Yanagita 1978;Liu et al 1999), physical dependence (Murano et al 1978;Yanagita 1978;Liu et al 1999;Leo et al 2000), and tolerance (Murano et al 1978) and can elicit a conditioned place preference (CPP) (Sprague et al 2002;Tzschentke et al 2002), whereas other studies have failed to demonstrate such effects (Richter et al 1985;Preston et al 1991;Miranda and Pinardi 1998). These conflicting reports regarding the abuse potential and dependence liability of TRAM have been attributed to nonselective actions at central opioidergic and monoaminergic systems.…”
Section: Introductionmentioning
confidence: 97%
“…These conflicting reports regarding the abuse potential and dependence liability of TRAM have been attributed to nonselective actions at central opioidergic and monoaminergic systems. In addition, depending on the dose, animal species and strain, and experimental procedures used to evaluate positively reinforcing effects, TRAM may have been considered either high, low, or even devoid of abuse potential (Sprague et al 2002;Tzschentke et al 2002).…”
Section: Introductionmentioning
confidence: 99%